Pemberdayaan Masyarakat dalam Upaya Penanggulangan Bencana Gempa Bumi dan Tsunami di Desa Palangkuma, Kecamatan Sirenja, Kabupaten Donggala - Seprius; Yudit; Dewi Sugiarti; Meyti; Moh Andri; Intan Fitrah Andini (BALE LITERASI, 2026)
Tompe Village is located on the western coast of Sirenja Subdistrict, Donggala Regency, in Central Sulawesi Province. It has experienced land subsidence, causing the land in Tompe Village to be lower than other areas after the 2018 earthquake. This study aims to describe the mitigation of earthquakes and tsunamis after the 2018 earthquake in Tompe Village, Sirenja District. This study is quantitative research using a pre-experimental method (pre-experimental design) of the one-group pre-test and post-test design, with treatment given only to one experimental group without using a control group for the community of Tompe Village in Sirenja District, Donggala Regency. The results of the analysis show a significant increase in community knowledge after education was provided (p = 0.000). A significance value of 0.000 on the action variable indicates that education has a real impact on community behavior when facing emergency situations. Unlike the two previous variables, the community's attitude variable did not experience significant changes after the educational intervention (p = 0.323).